Industrial attachment report with Exxonmobil Asia Pacific Pte Ltd - Zhang, Chen (2011)
This report documents the author’s training experience and course of learning during his Industrial Attachment (IA) period with Distributed Control System/Triple Modular Redundant (DCS/TMR) Section, Plant Computing Group (PCG), ExxonMobil Asia Pacific Pte Ltd. Report starts with an introduction of the company and the department the author is attached to. The emphasis is then moved towards the detailed analysis of the two TMR System Upgrade projects the author has been mainly involved in within his internship. The analysis is presented in the order of project progressing phases, which includes Logic Interpretation, Logic Conversion, Application Development, and Logic Testing. Report is finally concluded with the author’s acquisitions. This 22-week compulsory attachment program provides the author with the chance to apply what he learned into real-world applications. After this attachment, the author improves his technical knowledge on Control Engineering, as well as enhances his communication skill and problem-solving skill. The experience ignites the author’s interest in engineering field and helps to well prepare the author for his future career after graduation.